2013
DOI: 10.1186/1476-4598-12-98
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in immune-mediated inflammatory diseases (IMID)

Abstract: Inflammation and cancer have a profound yet ambiguous relationship. Inflammation - especially chronic inflammation - has protumorigenic effects, but inflammatory cells also mediate an immune response against the tumor and immunosuppression is known to increase the risk for certain tumors.This article reviews current literature on the role of inflammation in cancer and the cancer risk in immune-mediated inflammatory diseases (IMIDs). We discuss the effect on cancer risk of different drug classes used in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 139 publications
1
97
0
3
Order By: Relevance
“…The results of several studies have indicated that chronic inflammation can initiate tumor development by causing DNA damage or making cell susceptible to mutagens (29). Furthermore, inflammatory mediators, such as tumor necrosis factor, interleukin-1, interleukin-6, growth factors, chemokines, and proteases, can promote the development of cancer via proliferative, anti-apoptotic, and pro-angiogenic effects on the epithelium (30).…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies have indicated that chronic inflammation can initiate tumor development by causing DNA damage or making cell susceptible to mutagens (29). Furthermore, inflammatory mediators, such as tumor necrosis factor, interleukin-1, interleukin-6, growth factors, chemokines, and proteases, can promote the development of cancer via proliferative, anti-apoptotic, and pro-angiogenic effects on the epithelium (30).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of inflammation and immunity-mediated inflammatory diseases can result in inadequate and excessive immune response with cytokine disregulation and induction of acute or chronic immune reaction. These reactions can induce both pro-and antitumorigennic effects, which subsequently can persist and become inducer of progression or regression of cancer disease [1].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of these diseases is rather high and involves 5-7% of the population in developed countries. The need to constantly monitor the immune reactions of these patients is based on the high risk of development of cancer [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…52 An increased risk of non-melanoma skin cancer has been found associated with the use of a combination of anti-TNF and MTX in RA and with the use of PUVA, cyclosporine, and anti-TNF in psoriasis while the risk of melanoma is slightly increased. 53,54 Thus, biotherapies could be classified according to their potential oncogenic AEs.…”
Section: Anti-tnf and Anti-tnfr Antibodiesmentioning
confidence: 99%